RELASI AGAMA DAN NEGARA PERSPEKTIF AL-MAWARDI RELEVANSINYA DI INDONESIA - Toguan Rambe; Seva Maya Sari (IAIN Padangsidimpuan, 2021)
Discourses on issues of religion and state have attracted the attention of many Muslim scholars and are always interesting to study. This is because in Islam it is not explicitly explained. One of the highlights of this problem is Al Mawardi. Al Mawardi's political theories are considered to be relevant and provide sub-sanctions to regulate obedience. Indonesia, which involved religion in its establishment, is certainly very interesting when viewed from the theory put forward by Al Mawardi regarding the relationship between religion and state. The purpose of this study is to see the relevance of Al Mawardi's theory regarding the relationship between religion and state in Indonesia. The method used in this research is descriptive analytical with a non-interactive qualitative approach, namely the main data source is the book Al Ahkam Sulthaniyyah by Al Mawardi by looking at the relationship between religion and the state of Indonesia. The results of this study indicate that the relationship between religion and state as stated by Al Mawardi has relevance to the situation in Indonesia, although it is not entirely the same as that stated by Al Mawardi, at least with the accommodative attitude of the Indonesian government towards religion. Of course this can show the goodwill of the state in relation to religion. This finding can certainly add to the wealth of Islam in the state, so as to create a hearmonization of good relations between religion and state.